Retinal findings predictive of outcome in cerebral malaria. - Lewallen, S; Bakker, H; Taylor, T; Wills, B; Courtright, P; Molyneux, M (1996)
The pathogenesis of cerebral malaria is poorly understood. Direct and indirect ophthalmoscope examinations of 141 Malawian children with strictly defined cerebral malaria revealed 2 distinct and prognostically significant findings: papilloedema and extramacular retinal oedema. The relative risk of death in patients with papilloedema was 6.7 times that in patients without papilloedema. Extramacular retinal oedema was associated with a 2.9 fold increase in the relative risk of dying. The mortality rate in patients with neither of these signs was only 1.3% compared to an overall mortality rate of 9.2%. The clinical and laboratory features associated with each of these ophthalmological findings were different, suggesting that there may be at least 2 different pathogenetic processes in patients with cerebral malaria.